ANALISIS MOTIVASI MEMBER FITNESS POINT WORKOUT SPACE YOGYAKARTA: ANALISIS MOTIVASI MEMBER FITNESS POINT WORKOUT SPACE YOGYAKARTA - Kace Melwair Kace; Antonius Tri Wibowo (Universitas Mercu Buana Yogyakarta, 2024)
Exercise plays an important role in maintaining physical health and supporting body development. However, it is a fact that many people start exercising but are not consistent in doing so. One of the factors that influence exercise consistency is motivation. Based on this phenomenon, this study was conducted to analyze the motivation of Point Workout Space Yogyakarta members in exercising at the gym. Data were collected through interviews, observations, and documentation with a qualitative approach. The results showed that gym members' motivation is influenced by intrinsic factors such as interest and challenge, as well as extrinsic factors such as body appearance, fitness, and social interaction. However, obstacles such as injury and distance can reduce motivation. The research was conducted at Point Workout Space Yogyakarta for one week, with the main data sources from direct interviews, as well as documentation and observation. Data validation through source and method triangulation ensured the validity of the findings. The analysis showed that understanding members' motivational factors can help gym managers develop effective strategies to increase members' participation and satisfaction